Integrating storytelling into speaking assessment for public primary level learners - Gultom, Valerina Emma Hasian; Trisanti, Novia (ELT Forum: Journal of English Language Teaching, 2025)
This study reveals the integration of storytelling into the learning and speaking assessment process for students in public elementary schools, aiming to seek advantages and address the challenges of speaking assessments. Speaking skills are important for young learners, yet many face difficulties due to limited opportunities for practice and teacher-centered approaches. While storytelling has been known as an effective method to enhance language skills, its role as a formal speaking assessment tool remains underexplored in Indonesian schools. The research aims to investigate how to improve speaking skills and assess students' speaking abilities using storytelling. This study uses a qualitative and conceptual approach, reviewing relevant literature to gather insights on storytelling's effectiveness in language development and its potential as an assessment tool. The study found that storytelling significantly improves students' fluency, vocabulary, and pronunciation while creating a more relaxed and engaging environment for assessment. However, this study identifies challenges such as varying language abilities and student anxiety. The findings suggest that storytelling can offer a more authentic and dynamic method for assessing speaking skills, providing a valuable alternative to traditional assessments. The findings show that storytelling effectively, improves speaking skills and provides a more engaging and less intimidating method for assessing students' abilities.